Effect of agitation speed and aeration rate on fructosyltransferase production of Aspergillus oryzae IPT-301 in stirred tank bioreactor - Maiorano, Alfredo Eduardo; da Silva, Elda Sabino; Perna, Rafael Firmani; Ottoni, Cristiane Angélica [UNESP]; Piccoli, Rosane Aparecida Moniz; Fernandez, Rubén Cuervo; Maresma, Beatriz Guilarte; de Andrade Rodrigues, Maria Filomena (Springer Nature, 2020)
Objective: Fructooligosaccharides (FOS) are prebiotic substances that have been extensively incorporated in different products of food industry mostly for their bifidogenic properties and economic value. The main commercial FOS production comes from the biotransformation of sucrose and intracellular and extracellular microbial enzymes–fructosyltransferases (FTase). Aspergillus oryzae IPT-301 produces FTase. In order to increase its production, this study focuses on evaluating the effects of different agitation speed and aeration rates which affect yields in a stirred tank bioreactor. Results: Agitation had more influence on cell growth than aeration. The maximum intracellular FTase activity and the volumetric productivity of total intracellular FTase were obtained at 800 rpm and 0.75 vvm, and reached values of 2100 U g−1 and 667 U dm−3 h−1, respectively. The agitation speed had a strong influence on the activity of extracellular FTase produced which reached the maximum amount of 53 U cm−3. The higher value of total activity obtained was 22,831 U dm−3 at 0.75 vvm and 800 rpm. Conclusion: Aeration rates and agitation speed showed strong influence upon the growth and production of fructosyltransferase from Aspergillus oryzae IPT-301 in media containing sucrose as carbon source. The control of aeration rate and agitation speed can be a valuable fermentation strategy to improve enzyme production.
Keywords: Aspergillus; Enzyme production; Fructooligosaccharides; Fructosyltransferase; KLa; β-fructofuranosidase